Initial seroprevalence records of infectious agents implicated in reproductive issues in high-altitude cattle from two districts in cajamarca, peru. - Mendoza, J.E. (2024)
In high Andean regions with subsistence livestock farming, diagnostic studies are rarely conducted for reproductive issues in extensively bred cows. This research aimed to determine the seroprevalence of Neospora caninum, bovine viral diarrhea virus (BVDV),and bovine herpesvirus (BHV-1) in cattle above 3300 meters in Peru. Blood from 292 cattle across categories and breeds was collected. Antibody prevalence was 13.70±3.94% for N. caninum, 30.14±5.26% for BVDV, and 2.74±1.87% for BHV-1. District-wise differences were not significant (P>0.05). Cow and Creole breed were the most affected, but without statistical variance (P>0.05). These results confirm N. caninum, BVDV, and BHV-1 presence in reproductive issues in high altitudes cattle in Cajamarca and Celendín provinces.